PENGARUH PENERAPAN METODEROLE PLAYING TERHADAP HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN PKn KELAS V MIN - Warsiningsih, Indriyanti; Utami, Sri; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problem of this research is whether there is influence of Role Playing method implementation and how big influence to learners learning result in learning Vocabulary class V MIN Pontianak. Aims to describe the effect of Role Playing application and how much influence on students outcomes in learning V grade. The method used is experiment with Quasy Experimental Design Type Non Equivalent Control Group Design. Population is all learners class V MIN City Pontianak accredited A. Sampling is non probability sampling type of purposive sampling that students class V MIN Bangka Belitung. The technique used is measurement of written test in form of objective. Based on analysis, average of experimental and control class post-test is 85,44 and 82,41. Based on results of normality test using Chi Square formula normal distributed. Furthermore, the homogeneity test of data with Fhitung (1.02) <Ftable (1.86), stated homogeneous and continued t test with separated variance formula, obtained count (4.26)>table (1,6684) with dk =72, so Ha accepted. From result of effect size calculation, obtained Î´ Ì… equal to 0,31 with medium criterion. This shows that there is influence of Role Playing method implementation to learners' learning result in PKn V Learning of Pontianak City. Keywords: Role Playing Method, Learning Outcomes, Citizenship Education